Theory of Semiconductor Quantum Devices Microscopic Modeling and Simulation Strategies - Rossi, Fausto; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Primary goal of this book is to provide a cohesive description of the vast field of semiconductor quantum devices, with special emphasis on basic quantum-mechanical phenomena governing the electro-optical response of new-generation nanomaterials. The book will cover within a common language different types of optoelectronic nanodevices, including quantum-cascade laser sources and detectors, few-electron/exciton quantum devices, and semiconductor-based quantum logic gates. The distinguishing feature of the present volume is a unified microscopic treatment of quantum-transport and coherent-optics phenomena on ultrasmall space- and time-scales, as well as of their semiclassical counterparts.
Fundamentals of Semiconductor Materials and Devices -- Part I: Microscopic Modelling -- The Density-Matrix Approach -- Three Key Approximation Levels -- Generalization to Systems with Open Boundaries -- Part II: Simulation Strategies -- Direct or Deterministic Integration Techniques -- Monte Carlo or Stochastic Sampling -- Proper Combinations of Direct and Monte Carlo Schemes -- Part III: State-of-the-Art Quantum Devices - Key Examples -- Quantum-Well Infrared Photodetectors -- Quantum-Cascade Lasers -- Part IV: New-Generation Nanomaterials and Nanodevices -- Few-Electron/Exciton Quantum Devices -- Semiconductor-Based Quantum Logic Gates -- New Frontiers of Electronic and Optoelectronic Device Physics and Technology.
Keywords: Engineering; Computer engineering; Nanotechnology; Materials Science; Nanotechnology; Optics, Optoelectronics, Plasmonics and Optical Devices; Solid State Physics; Spectroscopy and Microscopy; Electrical Engineering; Engineering, general